The Role of Anti-PD 1 (Programmed Cell Death-1) (Pembrolizumab) in Hepatocellular Carcinoma: A Narrative Literature Review - Fitriani, Nelila Pasmah; Suyata (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Hepatocellular carcinoma (HCC) is a malignant tumor originating from liver cells, HCC occurs in around 85% of patients diagnosed with cirrhosis. Treatment options for HCC consider liver function, extrahepatic spread, invasiveness, and the number and size of nodules. HCC therapy options include surgical resection, liver transplantation, tumor ablation, transarterial therapy and systemic chemotherapy. Pembrolizumab is a second-line systemic therapy option for the treatment of HCC after sorafenib therapy. Pembrolizumab is a class of immune checkpoint inhibitors (ICIs) and more specifically works as a programmed cell death-1 (PD-1) inhibitor.